Community Empowerment through the AKSARA Education Program: A Case Study of the 'Pandawa' Youth Organization - Ali Yasin, Nur; Hakim, Abdul; Nurul Yaqin, Mohammad; Azzam Alfatoni, Ibnu; Fakhri Salim Kavabih, Muhammad (Prosperity: Journal of Society and Empowerment, 2025)
Illiteracy among the elderly remains a challenge in various regions in Indonesia, including Banyuwangi Regency, limiting their social and economic participation. This article examines the implementation of the AKSARA program, an independent effort to address this issue, run by the youth organization PANDAWA (Persatuan Pemuda Wangkal) in the Wangkal neighborhood of Kalipuro District. The purpose of this study was to examine the program's implementation and analyze its impact on improving literacy and reducing illiteracy among elderly participants. The study used a qualitative approach with a case study method. Data were collected through observation, in-depth interviews, and documentation studies, then analyzed thematically. The results showed that the program was implemented using a teacher-centered learning approach, three times a week for fifteen meetings, held in residents' homes. The material focused on basic reading and writing with patient tutoring. Despite facing challenges such as time constraints and participant characteristics, PANDAWA was able to overcome these challenges with solutions based on local wisdom and strong social ties. The novelty of this study lies in the documentation of a community-based empowerment model driven entirely by local youth initiatives. The findings suggest that youth can be effective agents of change in non-formal education and sustainable community development.